ANALISIS KINERJA KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI (STUDI PADA 12 KABUPATEN/KOTA DI KALIMANTAN BARAT TAHUN 2007-2010) - B01108029, Eddy Hermansyah (Jurnal Pembangunan dan Pemerataan, 2013)
This research is entitled: Financial Performance Analysis Of Economic Growth (Studies in 12 districts / cities in West Kalimantan in 2007-2010). The purpose of this research is to determine the financial performance districts / cities in West Kalimantan to see the Independence of Financial Ratios Region1 (IFRR1), Independence of Financial Ratio Region 2 (IFRR2), PAD Effectiveness Ratio (REPAD) and Spending Efficiency Ratio (SER) and see the effect of financial performance on Economic Growth (EG) in the implementation of regional autonomy and fiscal decentralization the edge of districts / cities in West Kalimantan. The data were analyzed financial data (budget) 12 districts / cities in West Kalimantan fiscal year during 2007-2010. The tool uses descriptive quantitative data analysis and pool regression with fixed effect model approach. The results showed that the ratio region1 financial independence and financial self-sufficiency ratio region2 likely to increase, the ratio of the effectiveness of PAD in 2010 tended to decrease and efficiency ratios tend to be inefficient expenditures. The results of the regression calculation shows that the ratio of variable regions financial independence significant negative effect on economic growth, the ratio of variable effectiveness of PAD and ratio of variabel regions financial independence have a positive and significant impact on economic growth, while variable expenditure efficiency ratio was not significant influential the economic growth of the district / cities in West Kalimantan years during 2007-2010. Keywords: financial performance, economic growth, regional autonomy.